Development and evaluation of three multienzyme isothermal rapid amplification assays for fowl adenovirus serotype 4 - Yin Dai; Yueyi Zhong; Fazhi Xu; Siqin Gu; Huiqin Zhou; Jieru Wang; Dongdong Yin; Lei Yin; Xuehuai Shen; Xiaocheng Pan; Xuelan Liu (Poultry Science, 2024)
Fowl adenovirus serotype 4 (FAdV-4) is the main causative agent of hydropericardium hepatitis syndrome (HHS), which has resulted in huge economic losses to the poultry industry in recent years. Hence, a rapid and simple visual detection method is needed for identification of FAdV-4. In this study, three multienzyme isothermal rapid amplification (MIRA) assays, basic MIRA, MIRA-qPCR and MIRA-LFD were developed for detection of FAdV-4. The amplification primers and reaction conditions were optimized, and the specificity and sensitivity of the assays were evaluated. The MIRA assays were specific for FAdV-4 with no cross-reaction with novel goose astrovirus, H9 subtype avian influenza virus, duck enteritis virus, Muscovy duck reovirus, or duck circovirus. The basic MIRA assay required only one primer pair and the reaction can be completed within 30 min at 36 °C. The MIRA-qPCR and MIRA-LFD assays were completed in 20 min with a minimum detection limit of 1 × 101 copies/μL and 1 × 102 copies/μL, respectively. The results of the MIRA-LFD assay can be observed directly with the naked eye, omitting the need for specialized instruments. The positive rate of three proposed MIRA assays were consistent with that of the conventional PCR assay. The MIRA assays are simple, rapid, and effective diagnostic tools for field detection of FAdV-4.